ASSESSING ORGANISATIONS’ READINESS TO ADOPT GREEN INFORMATION TECHNOLOGY: THE CASE OF A SOUTH AFRICAN INFORMATION TECHNOLOGY SERVICES VENDOR - Muranganwa, Isaac; Naidoo, Rennie (The South African Journal of Industrial Engineering, 2023)
Green information technology (IT) adoption is an important topic in the fields of information systems, business sustainability, and corporate social responsibility. This case study applies the green IT adoption model (GITAM) to perform a systematic and qualitative readiness assessment at a major South African IT services vendor. Thematic data analysis was used to analyse the data collected from managers and specialist IT staff. The assessment revealed that the main organisational adoption readiness barriers were the lack of a formal green IT policy, an unclearly defined green IT governance framework, and a lack of green performance management. The main drivers of adoption were economic imperatives and regulatory and ethical requirements. Interestingly, a contextual variable – an exogenous shock caused by COVID-19 and the robustness of the organisation’s crisis response during the pandemic – rapidly increased the rate of green IT adoption at the firm.